Acute circumflex artery total occlusion during ablation of septal premature ventricular contraction with radiofrequency energy - Myrda, Krzysztof; Wilczek, Krzysztof; Gąsior, Mariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2020)
The 28-year-old female patient was admitted to our clinic with symptomatic, frequent, drug-refractory (β-blocker/propafenone) premature ventricular contraction (PVC) (Figure 1 A). Both echocardiography and cardiac magnetic resonance showed normal values of cardiac chamber size and function, without valvular dysfunction. Using an electroanatomical 3D system (Carto 3 UniVu) and ablation catheter (Thermocool SmartTouch) (Biosense Webster, Diamond Bar, CA, USA), activation maps of both the right and left ventricles and the coronary sinus (CS), respectively, were created. Despite delivery of radiofrequency (RF) energy with 30–40 W to the interventricular septum from the left and right side the ablation was unsuccessful. Thus, based on the local signals, fluoroscopy view and 3D map, RF energy application was performed within the coronary sinus in the proximity of the posterior cardiac vein (MCV) (Figures 1 A–C). In the 60th s of the successful RF application with 20 W, signs of ischemia were present in the 12-lead electrocardiogram. Urgent coronarography showed acute occlusion of the distal circumflex artery (LCx) (Figure 1 D). Successful wire crossing and recanalization were achieved with the coronary guide wire. Prolonged inflation with a 2.25 × 12 mm semi-compliant balloon demonstrated a suboptimal result and therefore a 2.5 × 15 mm sirolimus-eluting stent (Orsiro, Biotronic AG, Büllach, Switzerland) was implanted, with an optimal angiographic result (Figure 1 E). At discharge and in 6 months’ follow-up, there was no evidence of recurrence of ventricular extra beats in 24-hour Holter monitoring. Based on the medical history, physical examination and the results of the additional tests, no signs of coronary artery disease were found.